De amarrar o facão a casa da ruindade: unidades fraseológicas nas áreas semânticas Ciclos da vida e Convívio e comportamento social no interior do Maranhão e do Ceará - SILVA, Nádia Letícia Pereira (2020)
Study of phraseological units based on data of a linguistic nature extracted from the corpus of the Atlas Linguistic Project of Brazil (ALiB) referring to the localities of the interior of Maranhão and Ceará that integrate the network of linguistic points of the Atlas, having as a starting point the assumption that phraseological units, as items in the lexicon, are strictly related to the socio-cultural facts of the linguistic communities in which they are inserted. The main objective is to investigate the phraseological units in Portuguese spoken in the interior of Maranhão and Ceará, in the semantic areas Life cycles and Social interaction and behavior, with a view to: (i) examining the productivity of these units in geolinguistic data; (ii) analyze its use considering the diatopic, diassexual and diagenational axes; (iii) check the dictionary of the units that make up the corpus; (iv) identify the structural typology of the documented phraseological units; (v) elaborate diatopic letters with the most productive phraseological units; (vi) prepare a glossary with the documented phraseological units; and (vii) offer subsidies for the construction of the VALEXTRA Project database. The work follows two theoretical methodological biases. Due to its geosociolinguistic nature, it is based on the principles of PluridimensionalGeolinguistics used by the ALiB Project team of researchers, in which the data record accommodates diatopic, diagenational, diasexual and diastratic parameters. As it is a research within the scope of Lexicology, linked to the Lexical Variation Project: theories, resources and applications: from lexical conditioning to pragmatic constructions (VALEXTRA), it takes Mejri's studies as a theoretical support (1997; 2012; 2017; 2018) ), Sfar (2016), Gross (1996) and Paim, Sfar and Mejri (2018), to address issues related to phraseological units, according to the French perspective. The study includes 19 linguistics points, eight from Maranhão and 11 from Ceará, thus having a total of 76 informants, all with incomplete elementary education, distributed equally among the 19 points and stratified by sex - man and woman; age - age group I, 18 to 30 years old, and age group II, 50 to 65 years old. 80 phraseological units were cataloged that reflect the speakers' discursive competence, which corroborates the idea that an expressive part of our discourse is made up of phraseologisms.